Analysis of Efficacy and Toxicity Profile of First-Line Sunitinib or Pazopanib in Metastatic Clear Cell Renal Cell Carcinoma in the Brazilian Population - Pedro Isaacsson Velho; Mirella Nardo; Manoel Carlos Leonardi de Azevedo Souza; Renata R.C. Colombo Bonadio; Guilherme Nader Marta; David Q.B. Muniz; Diogo Assed Bastos; Carlos Dzik (Journal of Global Oncology, 2018)
Purpose: Sunitinib and pazopanib are multitargeted tyrosine kinase inhibitors (TKIs) that act against vascular endothelial growth factor receptors and are standard first-line treatment options for metastatic clear cell renal cell carcinoma (ccRCC). The Brazilian public health system diverges from the randomized clinical trials in the availability of first and subsequent lines of treatment and in clinical and demographic characteristics of patients. Therefore, it is essential to describe the history of advanced ccRCC during and after TKI treatment in this population. Methods: We performed a retrospective analysis of patients with advanced ccRCC treated with a first-line TKI (either sunitinib or pazopanib) between February 2009 and March 2017 in a single academic Brazilian cancer center (Instituto do Câncer do Estado de São Paulo). Results: Of the 222 patients, 109 were treated with sunitinib and 113 with pazopanib. The median duration of treatment and overall survival (OS) were 6.4 and 15.2 months for sunitinib and 6.7 and 14.2 months for pazopanib, respectively. Discontinuation of treatment occurred secondarily to progressive disease or death in 64.2% of patients using sunitinib and in 54.8% of patients using pazopanib. Adverse events were responsible for discontinuation of treatment in 28.4% of patients in the sunitinib group and in 22.1% in the pazopanib group. According to Memorial Sloan-Kettering Cancer Center risk categories, the OS was 32.9 months, 15.9 months, and 8.1 months for low risk, intermediate risk, and poor risk, respectively (hazard ratio, 1.72; 95% CI, 1.13 to 2.26; P < .001). Conclusion: The use of TKI inhibitors as first-line treatment of metastatic RCC is effective and feasible in the Brazilian public health. However, the median OS of our population is considerably lower compared with the prospective trials that evaluated the same drugs.